AN ANALYSIS OF READING COMPREHENSION IN ENGLISH TEXTBOOKS AT HIGH SCHOOL GRADE XII IN INDONESIA - nisya anizar; Beatrik Nuyen Saragih; Tria Wahyuni Feronika Sinaga (Universitas Islam Nahdlatul Ulama Jepara, 2019)
AbstractThis study aims to determine the forms of text and the use of appropriate genres focusing on reading comprehension in English textbooks in high school in 12th grade. The form of this research is descriptive by comparing books and analyzing reading texts in the textbook